BESARNYA KETERBUKAAN LAHAN DI RKT 2016 WILAYAH PT. AYA YAYANG INDONESIA, KABUPATEN TABALONG - Ari Wahyudi; Ahmad Yamani; Gusti Seransyah Rudy (Universitas Lambung Mangkurat, 2019)
ABSTRACT. This research aims to gain information on the magnitude and forms of openness of the land due to the activities of TPTI in RKT 2016. Sample data retrival implemented in area IUPHHK-HA PT. Aya Yayang Indonesia, sub Muara Uya, Tabalong Regency, located on a swath of work 21U, 22U, 20V, 22V, and 21V. The objects of research are areas of IUPHHK-HA PT. Aya Yayang with the collected parameters is a form of land cover changes from forest into non-forest. The total number of samples as much as 66 samples. The research method used is a purposive sampling method and analyzed with overlay, overlay image interpretation results of GPS data, measuring Planimetris, the calculation of the level of openness and tabulate. Research resultsshowed the form of openness of the land in the form of roads logging, skid trails, camp production, TPn, a Bush/shrub and fields for activity outside the logging activities. The magnitude of the openness of the land due to the activities of the fifth on a swath of TPTI work of 58.42 Ha of the total area of the fifth working swath 500 Ha. The openness that could be assessed a percentage of openness just lay in theswath of 21V, due to have been 100% in working on logging. The vast openness of the land on a swath of 21V 26.98 ha with percentage of openness 26.98% of total area of 100 ha and is the swath of openness laha by category